Is There Hope after Despair? An Analysis of Trust among China's Cultural Revolution Survivors - Massimiliano Tani; Zhiming Cheng; Benno Torgler (Institute of Labor Economics (IZA), 2023)
We study the long-term effects of the Cultural Revolution, characterised by widespread violence, summary executions and chaos, on a set of trust outcomes among people surveyed by the China Survey in 2008. We find that the revolution, identified by cohort-specific exposure to excess deaths at the county level, has a significant long-term impact on trust. However, the effects differ according to the relationship considered. Overall, trust emerges as a binder between an individual and his/her friends and relatives, but as a divisive force between the same person and those with whom one may compete with (e.g., co-workers) and unknown or less known others (e.g., those living in the same town). As the revolution occurred more than four decades prior to the China Survey, the results do not support viewing the sole passing of time as an effective cure to recover from a prolonged traumatic experience.
Keywords: D3; 330; trust; Cultural Revolution; inside-outside groups